Vatican II : renewal within tradition - Lamb, Matthew L.; Levering, Matthew, 1971- (Oxford ; New York : Oxford University Press, 2008)
From 1962 to 1965, in perhaps the most important religious event of the twentieth century, the Second Vatican Council met to plot a course for the future of the Roman Catholic Church. After thousands of speeches, resolutions, and votes, the Council issued sixteen official documents on topics ranging from divine revelation to relations with non-Christians. In many ways, though, the real challenges began after the council was over and Catholics began to argue over the interpretation of the documents. Many analysts perceived the Council's far-reaching changes as breaks with Church tradition, and.
Part I. The Constitutions -- The dogmatic constitution on the church, Lumen Gentium -- 1. Nature, mission, and structure of the church / Avery Dulles -- 2. The universal call to holiness / Benoit-Dominique de La Soujeole -- The dogmatic constitution on divine revelation, Dei Verbum -- 3. Revelation and its transmission / Francis Martin -- 4. Inspiration and interpretation / Denis Farkasfalvy -- The constitution on the sacred liturgy, Sacrosanctum Concilium -- 5. Theology of the liturgy / Pamela E.J. Jackson -- 6. The sacraments of the church / Romanus Cessario -- The pastoral constitution onthe church in the modern world, Gaudium et Spes -- 7. Doctrinal perspectives on the church in the modern world / J. Brian Benestad -- 8. Pastoral perspectives on the church in the modern world / Matthew Levering -- Part II. The Decrees -- 9. The decree on the bishops' pastoral office in the church, Christus Dominus / Brian Ferme -- 10. The decree on the ministry and life of priests, Presbyterorum Ordinis / Guy Mansini and Lawrence J. Welch -- 11. The decree on priestly formation, Optatam Totius / Anthony A. Akinwale -- 12. The decree on the appropriate renewal of religious life, Perfectae Caritatis / M. Prudence Allen and M. Judith O'Brien -- 13. The decree on the apostolate of the laity, Apostolicam Actuositatem / Robert W. Oliver -- 14. The decree on the church's missionary activity, Ad Gentes / Francis George -- 15. The decree on ecumenism, Unitatis Redintegratio / Charles Morerod -- 16. The decree on the Eastern Catholic churches, Orientalium Ecclesiarum / Khaled Anatolios -- 17. The decree on the instruments of social communication, Inter Mirifica / Richard John Neuhaus -- Part III. The Declarations -- 18. The declaration on religious freedom, Dignitatis Humanae / F. Russell Hittinger -- 19. The declaration on Christian education, Gravissimum Educationis / Don J. Briel -- 20. The declaration on the relationship of the church to non-Christian religions, Nostra Aetate / Arthur Kennedy -- Commentary -- 20. Anamnesis, Epiclesis, Prolepsis : categories for reading the Second Vatican Council as "renewal within tradition" / Geoffrey Wainwright -- Concluding Reflections -- 22. The challenges of reform and renewal within Catholic tradition / Matthew L. Lamb.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Catholic Church -- Doctrines; Église catholique -- Doctrines; Catholic Church; RELIGION -- Christian Theology -- Ecclesiology; Theology, Doctrinal